NCERT Solutions Class 9 Mathematics

Exercise 2.3

Q.1. Find the remainder when x3 + 3x2 + 3x + 1 is divided by

(i) x + 1 (ii) x - 12 (iii) x (iv) x + π (v) 5 + 2x

Q.2. Find the remainder when x3 - ax2 + 6x - a is divided by x - a.

Q.3. Check whether 7 + 3x is a factor of 3x3 + 7x.

NCERT Solutions Class 9 Mathematics

Exercise 2.3

Q.1. Find the remainder when x3 + 3x2 + 3x + 1 is divided by

(i) x + 1 (ii) x - 12 (iii) x (iv) x + π (v) 5 + 2x

Solution:

The remainder can be obtained by either long division method or by remainder theorem.

(i) Dividing x3 + 3x2 + 3x + 1 by x + 1

p(x) = x3 + 3x2 + 3x + 1

g(x) = x + 1

Put g(x) = 0,

i.e., x+1 = 0 ⇒ x = -1

p(-1) = (-1)3 + 3(-1)2 + 3(-1) + 1

= -1 + 3 - 3 + 1 = 0

Therefore, the remainder is 0.

(ii) Dividing x3 + 3x2 + 3x + 1 by x - 12 

p(x) = x3 + 3x2 + 3x + 1

g(x) = x - 12

Put g(x) = 0,

i.e., x - 12= 0 ⇒ x = 12

p12 = 123+ 3122+ 312+ 1

= 18 + 34 +32 + 1

= 1+6+12+88 = 278

Therefore, the remainder is 278.

(iii) Dividing x3 + 3x2 + 3x + 1 by x 

p(x) = x3 + 3x2 + 3x + 1

g(x) = x

Put g(x) = 0, i.e., x = 0

p(0) = (0)3 + 3(0)2 + 3(0) + 1 = 1

Therefore, the remainder is 1.

(iv) Dividing x3 + 3x2 + 3x + 1 by x + π

Now p(x) = x3 + 3x2 + 3x + 1

g(x) = x + π

Put g(x) = 0, i.e., x = -π

p(π) = (-π)3 + 3(π)2 + 3(π) + 1

= -π3 +3 π2 -3 π + 1

Therefore, the remainder is -π3 +3 π2 -3 π + 1.

(v) Dividing x3 + 3x2 + 3x + 1 by 5 + 2x

Now p(x) = x3 + 3x2 + 3x + 1

g(x) = 5 + 2x 

Put g(x) = 0, i.e., x = - 52

p-52 = -523+ 3-522 + 3-52+ 1

= -1258 + 754 - 152 + 1

= -125+150-60+88 = -278

Therefore, the remainder is -278.

Q.2. Find the remainder when x3 - ax2 + 6x - a is divided by x - a.

Solution:

The remainder can be obtained by either long division method or by remainder theorem.

Using the remainder theorem,

p(x) = x3 - ax2 + 6x - a

g(x) = x - a

Put g(x) = 0, i.e., x - a = 0 ⇒ x = a

Now, p(a) = a3 - a × a2 + 6 × a - a

= a3 - a3 + 6a - a = 5a

Therefore, remainder will be 5a

Q.3. Check whether 7 + 3x is a factor of 3x3 + 7x.

Solution:

If we divide 3x3 + 7x by 7 + 3x and remainder comes out to be 0 then 7 + 3x will be a factor of 3x3 + 7x. The same can be checked by long division method or by factor theorem.

Using factor theorem,

p(x) = 3x3 + 7x

g(x) = 7 + 3x

Put g(x) = 0, i.e., 7 + 3x = 0

x = - 73

p-73 = 3-733 + 7-73

= -3439 - 493 = -343-1479

= -4909 ≠ 0

As remainder is not zero, 7 + 3x is not a factor of 3x3 + 7x.